2022
DOI: 10.1302/2633-1462.37.bjo-2022-0064.r1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical challenges, novel techniques, and systemic treatment of giant cell tumour of bone of the distal radius

Abstract: Aims Giant cell tumour of bone (GCTB) treatment changed since the introduction of denosumab from purely surgical towards a multidisciplinary approach, with recent concerns of higher recurrence rates after denosumab. We evaluated oncological, surgical, and functional outcomes for distal radius GCTB, with a critically appraised systematic literature review. Methods We included 76 patients with distal radius GCTB in three sarcoma centres (1990 to 2019). Median follow-up was 8.8 years (2 to 23). Seven patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…our study also showed that larger tumour size, higher campanacci grade, and the presence of a soft-tissue mass or a pathological fracture did not affect the rate of LR when evaluated across the entire cohort of 354 patients or the 267 treated by curettage. pathological fracture and campanacci stage were correlated with lr in other studies, 8,25,27,28 which differs from our observation, and may be related to population-based differences or technical aspects of surgical management. However, the presence of a pathological fracture or soft-tissue mass, factors which together define Campanacci grade 3 disease, are likely to contribute to surgical decision-making as their presence can make tumour removal by curettage and joint salvage more difficult, thereby pushing the treatment decision towards resection.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…our study also showed that larger tumour size, higher campanacci grade, and the presence of a soft-tissue mass or a pathological fracture did not affect the rate of LR when evaluated across the entire cohort of 354 patients or the 267 treated by curettage. pathological fracture and campanacci stage were correlated with lr in other studies, 8,25,27,28 which differs from our observation, and may be related to population-based differences or technical aspects of surgical management. However, the presence of a pathological fracture or soft-tissue mass, factors which together define Campanacci grade 3 disease, are likely to contribute to surgical decision-making as their presence can make tumour removal by curettage and joint salvage more difficult, thereby pushing the treatment decision towards resection.…”
Section: Discussioncontrasting
confidence: 96%
“…Even when joint sparing may be possible, GCTB of the distal radius carries the highest risk of LR, such that marginally salvageable joints may often best be treated with resection and fusion instead. 25,26 Not surprisingly, in this study, curettage of a GCTB in the distal radius had the highest rate of LR (33.3%) compared to all other sites combined (10.7%) (p = 0.043, Figure 7). By comparison, when GCTB involves expendable bones, the decision to proceed directly to resection is easier since this gives a low risk of recurrence with minimal associated morbidity.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations